2020
DOI: 10.3390/nu12061712
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Effect of Supplementation with Algae and Its Extracts on Glycolipid Metabolism: A Meta-Analysis of Randomized Controlled Trials

Abstract: Aims: The effect of algae and its extract supplementation on glycolipid metabolism has not been finalized. Therefore, the purpose of the meta-analyses was to assess the effects of its supplementation on glycolipid metabolism concentration. Methods: We have systematically searched PubMed, Web of Science, the Cochrane Library and Embase to identify randomized controlled trials (RCTs) that investigated the impact of algae and its extracts supplementation on glycolipid metabolism. Effect size analysis was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…It provided overall improvements to lipid metabolism, reduced inflammation, reduced or inhibited lipid accumulation, reduced or inhibited adipogenesis by downregulating genes involved in the process and activating AMPK, reduced insulin resistance and reduced the formation of ROS and lipid peroxidation both in humans and mice models of hyperlipidemia. These effects were also reported other recent reviews on marine polyphenols (Venkatesan et al 2019;Fernando et al 2020; Mateos, P erez-Correa, and Dom ınguez 2020).A meta-analysis by Ding et al (2020) of randomized clinical trials found that algae supplementation significantly reduced HDL and triglycerides levels but not LDL or total cholesterol.…”
Section: Hyperlipidemia and Obesitysupporting
confidence: 78%
See 1 more Smart Citation
“…It provided overall improvements to lipid metabolism, reduced inflammation, reduced or inhibited lipid accumulation, reduced or inhibited adipogenesis by downregulating genes involved in the process and activating AMPK, reduced insulin resistance and reduced the formation of ROS and lipid peroxidation both in humans and mice models of hyperlipidemia. These effects were also reported other recent reviews on marine polyphenols (Venkatesan et al 2019;Fernando et al 2020; Mateos, P erez-Correa, and Dom ınguez 2020).A meta-analysis by Ding et al (2020) of randomized clinical trials found that algae supplementation significantly reduced HDL and triglycerides levels but not LDL or total cholesterol.…”
Section: Hyperlipidemia and Obesitysupporting
confidence: 78%
“…CA was shown to increase the release of insulin on chronically hyperglycemic pancreatic b-cells (Bhattacharya et al 2014) and, as a supplement to a standard mouse diet, it was able to increase the levels of plasma insulin (Jung et al 2006;Chao et al 2010) and decreased the levels of blood glucose. Insulin levels in humans can also be improved by algae supplementation (Ding et al 2020).…”
Section: Hyperglycemiamentioning
confidence: 99%
“…4 It is well known that abnormalities in glucose and lipid metabolism often occur together, and numerous studies have shown that simultaneous control of glucose and lipid metabolism in the liver plays a very important role in the treatment of diabetes. 5…”
Section: Introductionmentioning
confidence: 99%
“…Thus, failure to detect and prevent T2DM in time may lead to serious complications, and pose a huge threat to life and health [ 49 ]. Usually, abnormal glucose metabolism and lipid metabolism often occur in parallel [ 50 ]. Afterward, consistent with previous studies [ 51 , 52 ], there were notable ( p < 0.001) increases in the levels of TC (13.82 ± 2.18 mmol/L), TG (2.11 ± 0.22 mmol/L), LDL-c (3.62 ± 0.56 mmol/L), TBA (11.84 ± 2.69 μmol/L), and FFA (2.24 ± 0.26 μmol/mL) in the DC group compared to the NC group, whereas there were no meaningful differences regarding HDL-c levels among the groups ( Figure 2 A–F).…”
Section: Resultsmentioning
confidence: 99%